Transformative Islamic Education Based on Hadith Values: Leadership Character Building Strategy for Santri - Amir, Sulaiman Muhammad; Harahap, Alwi Padly; Rahmi, Tutia; Nazmi, Khairin (Al-Fikru: Jurnal Ilmiah, 2024)
The lack of implementation of hadith values in shaping the leadership character of santri is a challenge for educators in Islamic educational institutions, because sources of value other than the Qur’an or hadith, certainly cannot be ensured to form Islamic character. In this regard, Dayah integrated Al-Muslimun Lhoksukon North Aceh implements character building through the values contained in the hadith. The method used in this research is qualitative based on narrative studies, with data collection techniques through observation, interviews, and documentation studies. The results revealed that the value of leadership character contained in the hadith is related to the value of justice, trustworthiness, and commitment which are characters that must exist in a leader. The implementation of character building is done through active learning, extra-curricular activities, problem-based learning. Determination is not only in terms of intellectual intelligence, but also spiritual and emotional. This research shows that the internalization of hadith values strengthens the leadership character of students, so Islamic educational institutions need to adopt this method to produce leaders with good character.